Intervention Proposal for Infant Prognathism: A Case Report in a Non-Syndromic Pediatric Patient - Chedid, Silvia J.; Húngaro, Renata (International Journal of Innovative Research in Medical Science, 2021)
Treating Class III malocclusions has been presently considered one of the most challenging and complex interventions of orthodontic daily practice. In this study, we report a case of a 17-month-old female patient, initially diagnosed with Angle Class III malocclusion, mandibular protrusion, and without genetic syndromes. Upon initial admission at the dental office, patient’s parents reported an inadequate bite pattern while the patient tried to eat solid food. Upon dental examination, a negative overjet of 8 millimeters was noticed and a two-phased treatment plan was established: 1. Performance of functional exercises; 2. Implementation of protractor device associated with masticatory guidance exercises. Radiographic examination and cephalometric analyses were performed throughout the case follow-up. Overall, the digital compression protocol carried out reverted the primary mandibular protrusion of -8 millimeters to +1 millimeters overbite, during the 6 months of treatment. In addition, the use of premaxillary protractor appliance increased the overbite to + 2 millimeters. The patient responded satisfactory to the treatment plan performed, and after 2 years, a proper primary occlusion, oral functionality, and facial aesthetics were improved.